INSPIRED but Tired: How Medical Faculty’s Job Demands and Resources Lead to Engagement, Work-Life Conflict, and Burnout - Lee, Rebecca S.; Son Hing, Leanne S.; Gnanakumaran, Vishi; Weiss, Shelly K.; Lero, Donna S.; Hausdorf, Peter A.; Daneman, Denis (Frontiers in Psychology, 2021)
The current study investigates physicians’ experiences of well-being (engagement, empowerment, work-life facilitation) and ill-being (work-life conflict, facilitation, burnout). Qualitative thematic analysis was used to analyze 30 interviews from medical faculty at a top research hospital in Canada. Our findings revealed that many medical faculty’s experiences of work-life conflict were severe while work-life facilitation was often a wishful platitude. The results of our analyses provide unique contributions to the literature. It appears that the job demands faculty face have coalescing (i.e., interactive) effects on their stress and work-life conflict. Further, we found that job resources play a dual-role for work-life conflict. Whereas supportive job resources (e.g., coworker support) directly lessen the burden of demands, stimulating job resources (e.g., challenging work) provide faculty a sense of psychological empowerment, lead to engagement, and motivate them to reinvest in their jobs, ultimately leading to greater work-life conflict. In addition, however, the great psychological empowerment that medical faculty experience appears to protect them from full burnout. Finally, we found that medical faculty engage in cognitive reappraisal strategies to mitigate their experiences of work-life conflict and its harmful consequences.